Perception of Mechanical Engineering Technician Students and Teachers towards Methods Applied at Technical Training institutes in Kenya - Lumumba , Wycliff; Kisilu , Kitainge; Dimo , Herbert (African Journal of Education,Science and Technology (AJEST), 2020)
Studies in Kenya show that teachers were more comfortable teaching theory than practical skills. The curricula in majority of Technical and Vocational education and training Institutions (TVET) is a theory based, where teachers use traditional teaching methods and that the graduates from the TVET institutions have low level of skills among other problems. The purpose of this study was to identify teaching methods used by instructors to deliver content in the departments of mechanical engineering in TVET institutions in Kenya, to establish the opinion of instructors about the teaching methods that they considered interesting, beneficial and motivating to students, to identify teaching strategies used in mechanical engineering department in TTIs in Kenya. This study adopted mixed research method, which used both quantitative and qualitative methods to give a general picture of the state of teaching methods used in Technical Training institutes in Kenya. In order to achieve the objectives, a sample comprising of 248 mechanical engineering technician students and 61 instructors was selected. Five technical training institutions were purposefully sampled and the respondents for the research were selected proportionately to the population in each institution. Self-administered questionnaires were filled by students and teachers / instructors using semi-structured questionnaires containing mainly the Likert-type rating scale observation scales. Data was analyzed descriptively using SPSS version 20 to generate frequencies, percentages, and correlation coefficients to help answer the research questions regarding different objectives. The results of the study showed that despite the availability of many teaching methods, teachers / instructors of TTIs are still using traditional approaches where the teacher’s / instructors’ role is directive and authoritative. The study also revealed that the instructors were aware of new constructivist methods of teaching and learning methods such as active learning, students having discussions with their teachers in order to construct their own knowledge, knowledge being a progressive process and students working in groups but the implementation of these approaches has not been well used and the teachers claiming that to use them will require a complete review of the Kenya National Education Curriculum which evaluates the learners mainly by written examinations. The study found out that no single teaching method is effective but found out that effective teaching methods are ones that will enable the instructor to attain the TVET objectives and also to complete the mechanical engineering syllabus within the time allocated by the Kenya Institute of Curriculum Development. The study recommends the adoption of student-centred teaching methods and further suggests constructivism as a method of instruction in order to give students time to develop instincts and manipulative skills.